Dos bytes aos átomos: reflexões e experimentações artísticas sobre o universo da impressão 3D - Nunes, Soraya Cristina Braz [UNESP] (2014)
The emergency of a new production technology, the 3D printing, has been considered by enthusiasts as a “New Industrial Revolution” for confronting the industry paradigms such as mass production. This technology consists in the transposition of three-dimensional digital models into physical objects and becomes popular thanks to virtual communities that actively share information. 3D printing has become a hotbed of experimentation for artists, both for those who were already working with digital media and wanted to materialize their creations, and for those who set out to explore new paths through the possibility of dialogue between digital and physical. Many works of art can demonstrate some optimism about the supposed revolutionary power of this new technology, or discuss the implications of its possible uses in society. In this context, this research considers the proposals of some of those works of art, and presents the art project “Deliberator”: a poetic reflection on the emergence of wiki-weapons, and unexpected use for 3D printing.